Simultaneous employment and depressive symptom trajectories around retirement age in Chile. (19th May 2022) - Madero-Cabib, Ignacio; Azar, Ariel; Guerra, Josefa
Abstract: Objectives: Over the last decade, an increasing number of empirical studies have examined long-term patterns of depression among adults around retirement age and identified employment status as a crucial determinant. However, most research has examined associations between cross-sectional measures of employment and prospective depression patterns, overlooking the changing nature of employment statuses, particularly close to retirement age. Furthermore, most knowledge in this field comes from studies conducted in developed countries in Western Europe and North America. To address these gaps, this study examined simultaneous trajectories in the employment and depressive symptom domains among two age groups of Chileans before and after the standard retirement age. Method: Using population-representative data and longitudinal statistical methods, we identified different trajectory types among two age groups (one aged 56–65 and another aged 66–75, at baseline) and characterized them according to social and health characteristics. Results: We found that trajectories defined by permanent employment were accompanied by lower depressive symptoms than trajectories indicating either retirement or inactivity. However, trajectories combining employment and the absence of depressive symptoms were primarily followed by individuals with advantaged health and social statuses at the baseline. Conclusion: Public policies aimed at promoting the mental health of older adults through their labor market integration risk forcing individuals who have accumulated social and health disadvantages across the life course to work longer.